Traction Resistance of the Front Plow Angle (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
With the help of frontal plug housings, the left and right upper edges of the overturned panels are first cut with an angle cutter, which eliminates the difficulties in the overturning process and reduces the traction resistance. Calculations based on theoretical studies showed that the tensile strength of the angle grinder should be in the range of 0.36-0.39 kN in the speed range of 1,8-2,3 m/s. The pulling resistance of the plug depends on the processing depth and coverage width of the angle cutter, and it showed that the processing depth should be 10-12 cm and the coverage width should be 10-12 cm in order to ensure the high quality of the technological process with low energy consumption.